(untitled) (GENDER EQUALITY: International Journal of Child and Gender Studies, 2019)
The terms gender and sex are often overlapped. The term sex in our society is often used in a dual sense. One of the factors that influence the occurrence of gender disparities is due to the variety of interpretations of the definition of gender itself. Often gender is equated with sex (sex), and the division of roles and responsibilities of each has been made in such a way and passed from year to year even from century to century, even the role of gender by society is then believed as if it was God’s nature.